When do people exploit moral wiggle room? An experimental analysis in a market setup - Katharina Momsen; Markus Ohndorf (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2019)
We investigate if decision makers exploit moral wiggle room in green market settings. We therefore implement a laboratory experiment in which subjects purchase products associated with externalities. In six between-subjects treatments, we alter the availability of information on the externalities, the price of revealing information as well as the nature of the externality, which could either affect another subject or change the amount spent by the experimenters on carbon offsets. We find that subjects do not exploit moral wiggle room when revealing information is costless. When a very small cost of revealing information is introduced, their behavior depends on the relation between prices and externalities. In situations in which it is relatively cheap to have a large impact on the recipient's payoff, subjects exploit moral wiggle room in order to choose selfishly. For other parametrizations, subjects behave either honestly egoistically or altruistically.
Keywords: C91; D12; D64; D89; Q50; 330; Information avoidance; experiment; carbon offsets; moral wiggle room; ethical consumption